The incorporation of spent coffee grounds as an additive in cement ventilation blocks - Khairul Anuar, Shahid; Vignesh, Ganesh; Norhaiza, Ghazali (Bentham Open, 2024)
Introduction: The growing coffee industry has created a lot of waste in the form of spent coffee grounds (SCG), mainly disposed of through landfills. Recycling them into concrete construction products helps reduce their carbon effect on the atmosphere. According to earlier investigations, the SCGs have potential usage as supplemental construction materials across various civil engineering applications. However, the absence of thorough research and successful practical implementations in the sector necessitate further detailed studies in ventilation block application. Aims: This study investigates the workability, compressive strength, water absorption and thermal performance of cement mortar containing different percentages of SCG in ventilation block production. Methods: Cement, sand, and water with the 1: 2.75: 0.6 ratio and different percentages of SCG are used in the mortar mix as additives. The specimens were cast in cubes (50 mm x 50 mm x 50 mm) to investigate the workability, strength, water absorption and dry density. Further, the ideal mix was chosen to produce ventilation blocks. The prototype cubicles made from the SCG ventilation blocks were used for continuous indoor temperature monitoring. Results: The results show that adding high amounts of SCGs into mortar has decreased workability and compressive strength in cement mortar blocks. However, the water absorption has reduced with the increased percentage of SCG added to the mix. Based on the results, the SCG0.75 is the most suitable ratio to be used as it showed a flowability of 48%, a compressive strength of 12.574 MPa and water absorption of 6.107%, which is ideal for producing the ventilation block. In addition, the temperature monitoring results showed a reduction in the indoor temperature that used the SCG ventilation block. Conclusion: This result suggests incorporating SCG in the ventilation block requires a suitable percentage of the SCG to fulfill the workability and strength of the block. Nevertheless, it may reduce indoor temperature, thus providing better thermal comfort. This study enables the SCG waste products to be used as sustainable materials in ventilation block production.